The Future of Aging Pathways to Human Life Extension - Fahy, Gregory M.; West, Michael D.; Coles, L. Stephen; Harris, Steven B.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Just as the health costs of aging threaten to bankrupt developed countries, this book makes the scientific case that a biological "bailout" could be on the way, and that human aging can be different in the future than it is today. Here 40 authors argue how our improving understanding of the biology of aging and selected technologies should enable the successful use of many different and complementary methods for ameliorating aging, and why such interventions are appropriate based on our current historical, anthropological, philosophical, ethical, evolutionary, and biological context. Challenging concepts are presented together with in-depth reviews and paradigm-breaking proposals that collectively illustrate the potential for changing aging as never before. The proposals extend from today to a future many decades from now in which the control of aging may become effectively complete. Examples include sirtuin-modulating pills, new concepts for attacking cardiovascular disease and cancer, mitochondrial rejuvenation, stem cell therapies and regeneration, tissue reconstruction, telomere maintenance, prevention of immunosenescence, extracellular rejuvenation, artificial DNA repair, and full deployment of nanotechnology. The Future of Aging will make you think about aging differently and is a challenge to all of us to open our eyes to the future therapeutic potential of biogerontology.
and Orientation -- Bridges to Life -- Analyzing Predictions: An Anthropological View of Anti-Aging Futures -- Towards Naturalistic Transcendence: The Value of Life and Life Extension to Persons as Conative Processes -- The Ethical Basis for Using Human Embryonic Stem Cells in the Treatment of Aging -- Evolutionary Origins of Aging -- Precedents for the Biological Control of Aging: Experimental Postponement, Prevention, and Reversal of Aging Processes -- The Future of Aging -- An Approach to Extending Human Lifespan Today -- Near Term Prospects for Ameliorating Cardiovascular Aging -- Near Term Prospects for Broad Spectrum Amelioration of Cancer -- Small Molecule Modulators of Sirtuin Activity -- Evolutionary Nutrigenomics -- Biological Effects of Calorie Restriction: Implications for Modification of Human Aging -- Calibrating Notch/TGF-? Signaling for Youthful, Healthy Tissue Maintenance and Repair -- Embryonic Stem Cells: Prospects of Regenerative Medicine for the Treatment of Human Aging -- Maintenance and Restoration of Immune System Function -- Mitochondrial Manipulation as a Treatment for Aging -- Life Extension by Tissue and Organ Replacement -- Telomeres and the Arithmetic of Human Longevity -- Repairing Extracellular Aging and Glycation -- Methuselah$1 (Bs DNA: Defining Genes That Can Extend Longevity -- Reversing Age-Related DNA Damage Through Engineered DNA Repair -- WILT: Necessity, Feasibility, Affordability -- Comprehensive Nanorobotic Control of Human Morbidity and Aging.s
Keywords: Medicine; Biotechnology; Nanochemistry; medicine -- Philosophy; Geriatrics; Biomedicine; Biomedicine general; Biotechnology; Nanochemistry; Philosophy of Medicine; Geriatrics/Gerontology.